Barriers to and Facilitators of a Career as a Physician‐Scientist Among Rheumatologists in the US. Issue 9 (September 2015) - Ogdie, Alexis; Shah, Ami A.; Makris, Una E.; Jiang, Yihui; Nelson, Amanda E.; Kim, Alfred H. J.; Angeles‐Han, Sheila T.; Castelino, Flavia V.; Golding, Amit; Muscal, Eyal; Kahlenberg, J. Michelle; Barg, Frances K.; et al.
<x xml:space="preserve">Abstract</x> Objective To determine perceived barriers to and facilitators of a career in rheumatology research, examine factors leading rheumatologists to leave an academic research career, and solicit ways to best support young physician‐scientists. Methods A web‐based survey was conducted among the domestic American College of Rheumatology (ACR) membership from January through March 2014. Inclusion criteria were ACR membership and an available e‐mail address. Non‐rheumatologists were excluded. The survey assessed demographics, research participation, barriers to and facilitators of a career in research, reasons for leaving a research career (when applicable), and ways in which the ACR could support junior investigators. Content analysis was used to extract relevant themes. Results Among 5, 448 domestic ACR members, 502 responses were obtained (9.2% response rate). After exclusions (38 incomplete, 2 duplicates, 32 non‐rheumatologists), 430 responses were analyzed. Participants included fellows, young investigators, established investigators, mentors, clinicians, and those who previously pursued a research career but have chosen a different career path. Funding and mentoring were the most highly ranked barriers and facilitators. Protection from clinical and administrative duties, institutional support, and personal characteristics such as resilience and persistence were also ranked highly. The most commonly cited reasons for leaving an academic research career were difficulty obtaining funding and lack of department or division support. Conclusion This is the first study to examine barriers to and facilitators of a career in rheumatology research from the perspectives of diverse groups of rheumatologists. Knowledge of such barriers and facilitators may assist in designing interventions to support investigators during vulnerable points in their career development.